German economy remaining strong amidst uncertainties - Claus Michelsen; Martin Bruns; Marius Clemens; Max Hanisch; Simon Junker; Konstantin A. Cholodilin; Thore Schlaak (DIW Weekly Report, 2019)
Although the economic boom in Germany is over, a recession is not looming. The economy is still expected to grow by 1.0 percent this year despite its recent weaker performance. Consumption remains a mainstay of the economy; the average annual increase in the number of employees is likely to be just under half a million. At 1.5 percent, inflation is barely dampening purchasing power and together with fiscal policy stimuli, it will lead to a noticeable increase in private consumption. Foreign demand, on the other hand, is developing moderately due to China's weakening economy and the fact that the industrial sector is losing momentum in many important export markets. The enormous political risks will dampen corporate investment as well.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook